1998
DOI: 10.1210/en.139.4.1972
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Retinoic Acid Receptor-  Sensitizes Prostate Cancer Cells to Growth Inhibition Mediated by Combinations of Retinoids and a 19-nor Hexafluoride Vitamin D3 Analog

Abstract: Retinoids and analogs of vitamin D3 may achieve greater in vivo applications if the toxic side effects encountered at pharmacologically active doses could be alleviated. These seco-steroid hormones often act in concert, and therefore, we attempted to dissect these interactions by isolating combinations of receptor-selective retinoids and a potent vitamin D3 analog [1alpha,25(OH)2-16ene-23-yne-26,27,F6-19nor-D3, code name LH] that were potent inhibitors of prostate cancer cell growth at low, physiologically saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 0 publications
3
39
1
Order By: Relevance
“…This is intriguing because PC-3 cells are more transformed than LNCaP cells (Carrol et al, 1993;Gaddipati et al, 1994;Issacs et al, 1994;Ewing et al, 1995;Tamimi et al, 1996) and, in particular, do not express RAR-β, whereas LNCaP cells do. This is possibly reflected by the reduced sensitivity of PC-3 cells to LH and various retinoids as found in the present study, and more comprehensively in the previous one (Campbell et al, 1998b). Strikingly, in PC-3 cells, antiproliferative potency appears to be retained by anti-AP-1 retinoids in combination with LH.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This is intriguing because PC-3 cells are more transformed than LNCaP cells (Carrol et al, 1993;Gaddipati et al, 1994;Issacs et al, 1994;Ewing et al, 1995;Tamimi et al, 1996) and, in particular, do not express RAR-β, whereas LNCaP cells do. This is possibly reflected by the reduced sensitivity of PC-3 cells to LH and various retinoids as found in the present study, and more comprehensively in the previous one (Campbell et al, 1998b). Strikingly, in PC-3 cells, antiproliferative potency appears to be retained by anti-AP-1 retinoids in combination with LH.…”
Section: Discussionsupporting
confidence: 81%
“…Previously, we have shown synergistic inhibition of prostate cancer cell proliferation by LH and certain novel and naturally occurring retinoids, and that a loss of synergistic inhibition correlated with loss of expression of RAR-β (Campbell et al, 1998b). However, this previous study was not able to assess to what extent the anti-AP-1 effects of retinoids contributed to the inhibitory behaviour.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The lack of ATRAinduced CYP26 in both PC3 and DU145 cells may be due to the loss of RARs in these cell lines. Several investigators have reported that the loss of RAR signaling in many epithelial tumours is driven by loss of expression of RARs (Campbell et al, 1998;Zhang, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The interactions of two compounds were assessed by measuring the mean effect of either compound acting alone (F SE; refs. 20,21,33). The combination of the mean effect for each compound acting alone was the predicted combined inhibition.…”
Section: Methodsmentioning
confidence: 99%